The Contribution Of Foot Reaction Speed And Dynamic Balance To The 100-M Running Speed Of FIK UNM Makassar Students - Andi Rizal (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study is a descriptive research that aims to determine the contribution of foot reaction speed and dynamic balance to the 100-meter running speed of FIK UNM Makassar students. This research was carried out on the student population of FIK UNM Makassar, using a random sample of 60 people. Data collection used foot reaction speed measurement instruments, dynamic balance tests, and 100-meter running tests. Data analysis used regression coefficient analysis techniques. And from the results of the data analysis, it can be concluded as follows: (1) There is a significant contribution of the reaction speed of the feet to the running speed of 100 meters in FIK UNM Makassar students. 57.1% (p=0.000). (2) There is a significant contribution of dynamic balance to the 100-meter running ability of FIK UNM Makassar students. By 36.8% (p = 0.000). (3) There is a significant contribution of the combination of leg reaction speed and dynamic balance to the 100-meter running ability of FIK UNM Makassar students. 62.0 % and F = 46.589 (p=0.000).